2000
DOI: 10.1103/physrevlett.85.2981
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Mediated Long-Range Oscillatory Interaction between Adatoms: Cu/Cu(111)

Abstract: A quantitative study of the long-range interaction between single copper adatoms on Cu(111) mediated by the electrons in the two-dimensional surface-state band is presented. The interaction potential was determined by evaluating the distance distribution of two adatoms from a series of scanning tunneling microscopy images taken at temperatures of 9 -21 K. The long-range interaction is oscillatory with a period of half the Fermi wavelength and decays for larger distances d as 1͞d2 . Five potential minima were i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
345
4
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(367 citation statements)
references
References 24 publications
17
345
4
1
Order By: Relevance
“…Our recent kinetic Monte Carlo simulation studies of island nucleation and growth show that this is the case [23,26]. Recent experimental STM studies have begun to probe the role of adsorbate lateral interactions in determining the structure of adsorbate islands at surfaces [9,29]. Theoretical-experimental interplay in this area would be fruitful.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent kinetic Monte Carlo simulation studies of island nucleation and growth show that this is the case [23,26]. Recent experimental STM studies have begun to probe the role of adsorbate lateral interactions in determining the structure of adsorbate islands at surfaces [9,29]. Theoretical-experimental interplay in this area would be fruitful.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Einstein and Schrieffer showed in tight-binding calculations that the intermediate-range interaction is present and is, in fact, more significant than the long-range interaction [3]. Recent, low-temperature STM studies also indicate that this is the case [9] for Cu adatoms on Cu(111). The intermediate range is accessible to modern, electronic-structure calculations.…”
Section: Introductionmentioning
confidence: 92%
“…Most notably, for the (111) face of noble metals, there is a circular surface state at the center of the surface Brillouin zone, leading to circularly isotropic interactions with a Fermi wavelength of order 3 nm. for Cu [10][11][12]. (These TABLE I.…”
Section: Review Of Indirect Interactionsmentioning
confidence: 99%
“…Ordered structures of atoms and molecules can be generated either by the manipulation of single atoms or molecules 1,2 by means of the tip of a scanning tunneling microscope ͑STM͒ or by using selfassembly processes of particles. [3][4][5][6] Recent experimental and theoretical studies have indicated that the long-range interactions ͑LRIs͒ between adsorbates on metal surfaces [7][8][9] can be exploited to create a new nanostructures. 10,11 Such interactions are caused by the quantum interference of surface-state electrons scattered off adsorbates.…”
Section: Introductionmentioning
confidence: 99%